Decarbonising City Precincts: An Australian Perspective - Bunning, Jessica; Beattie, Colin; Rauland, Vanessa; Newman, Peter (Springer, 2014)
The need to decarbonise the economy can be greatly assisted if precinct scale city development can be a focus. The new low carbon technology for energy, water and waste are favoured by the precinct scale, especially the the use of trigeneration, renewables, recycle wastewater, collecting rain water, waste to energy plants and automated solid wast collection. However, to make this work will require much more attention to the proper frameworks for carbon accounting and acknowledgement of best practice at precinct level. Governance will need to refocus on this smaller scale of delivery as it is not available at this moment. New models are developing that enable low carbon precincts to operate with a degree of independence within a broader centralised utility structure. Australian illustrations, specially from the City of Sydney, are showing that it is a feasible transition though some kind of new carbon credits for urban development need to be created.